Tributação sobre o download de softwares: novos dilemas da relação entre o fisco e o contribuinte - Fernandes, Emanuell Fernando Goiana (2019)
Contemporary society lives with an intense flow of information and goods through virtual environments. Thus, the communication of people and the transactions of goods through the world wide web has been of to repetitive to the world economy, society, and politics since computers were designed in the context of World War II. As a clear expression of the importance of this virtual network is the figure of software, that is, instructions that serve as guidelines for the operation of computers and which can be marketed or assigned in their use through the web. Moreover, as a consequence of the age of modern computing, current human relationships based on the virtual flow of information, goods and services, such as newspapers and virtual books, software, and online banking, are notorious. Thus, a means of disposing of the software, as goods subject to commercialization, was developed through the direct download on the machine of the computer program acquired in the virtual environment where it was acquired (download). Given the controversies presented regarding the legal nature of software commercialization, it is observed that most of the jurisprudential and legislative provisions on this subject are very inaccurate and even outdated. This, therefore, represents, on the one hand, legal uncertainty for taxpayers present in this branch of economic activity and, on the other hand, represents a hindrance to the State's taxing activity. Finally, we propose some solutions to the problems presented, without intending to exhaust the issue in question, but rather to arouse more studies on this theme.